The Effect of Internal Organization Factor and Legal Protection on User Intention of Whistleblowing System with Internal Control as Moderation Variable - Theresia Dwi Hastuti; Ridwan Sanjaya; Benediktus Danang Setianto (Soegijapranata Catholic University, 2023)
This research aims to analyze the influence of perceived organizational support, commitment to the organization, locus of control and law enforcement on whistleblowing intentions with internal control as a moderating variable. The sample for this research was the university academic community who live in Semarang, Central Java, Indonesia, totaling 246 people. This study investigates the motivations of university whistleblowers with the notion that as establishments are required to uphold sound governance practices, colleges ought to be free from fraud. Apart from that, research related to whistleblowing and legal protection moderated by internal control systems at universities is still underrepresented in Indonesia, so this moderation model is the originality of this research. The results of this study show that while organizational commitment, organizational support, and law enforcement have little impact on whistleblower intentions, locus of control does. The impact of legal protection on the desire to come out as a whistleblower may be mitigated by the internal control system. However, the impact of organizational commitment, support, and locus of control on the desire to become a whistleblower cannot be mitigated by the internal control system.